2022
DOI: 10.1097/j.pain.0000000000002592
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of monosodium glutamate induces sexually dimorphic headache- and nausea-like behaviours in rats

Abstract: Ingestion of monosodium glutamate (MSG) causes headache, nausea, and craniofacial tenderness in healthy individuals. The present study explored whether MSG produces behavioural signs of headache, nausea, and changes in craniofacial sensitivity in rats. The behavior of male and female Sprague-Dawley rats was video recorded before and after intraperitoneal (i.p.) injections of MSG (1-1000 mg/kg), nitroglycerin (GTN, 10 mg/kg), or normal saline. Behaviors (grimace score, head-flicks, rearing, head scratches, faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…3 a). Consistent with our previous results, males were found to exhibit a substantially greater increase in LOB duration compared to females 7 . In females, there was no significant effect of MSG treatment on LOB behaviour (Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…3 a). Consistent with our previous results, males were found to exhibit a substantially greater increase in LOB duration compared to females 7 . In females, there was no significant effect of MSG treatment on LOB behaviour (Fig.…”
Section: Resultssupporting
confidence: 92%
“…We have previously found that MSG (1000 mg/kg, i.p.) significantly suppresses normal exploratory and grooming (facial grooming and head scratch) behaviours compared to saline control 7 . There was a significant effect of time (F (4.510, 297.7) = 3.088; p = 0.0126), but no significant effect of treatment (F (5, 66) = 1.365; p = 0.2487) or time/treatment interaction (F (25, 330) = 0.9124; p = 0.5883) for facial grooming behaviour (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations